EDUKASI LITERASI FUNGSI DAN UPAYA PELESTARIAN MANGROVE DI WILAYAH PESISIR - Lewerissa, Yona Aksa; Hulopi, Mahriyana (Balobe: Jurnal Pengabdian Masyarakat, 2024)
The waters of Hunuth Village are one of the mangrove habitats Inner Ambon Bay. Still, as the population increases, various activities occur such as boat moorings and ships, which impact the growth and reduction of mangroves. The Community Service activity aims to provide knowledge and enhance the role of students from Christian Elementary School 1 Hunuth in preserving the mangrove ecosystem. Literacy education was conducted using a variety of methods, including lectures, video screenings, games, student storytelling, and the distribution of x-banners about mangroves. From the evaluation results through pre-and post-tests, there was an increase in knowledge, and it is hoped that through this activity, students can be motivated to become "sustainable ambassadors" playing an important role in maintaining the sustainability of mangroves in coastal areas.